The economic benefits of EU membership : an Empirical analysis - Zhitina, Anna; Klosová, Anna, 1942-; Villaverde Castro, José; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This master thesis is devoted to the empirical analysis of the economic benefits of EU membership. The analysis aims to investigate what is the impact of EU membership on growth of the real GDP (in constant prices), unemployment rate and inflation rate for 16 states entering EU after the year 1995 (analysed period of years is 1991-2014). The applied method for evaluation in the current work is econometric analysis of panel data. The first part of the thesis is devoted to the literature review. The second part is describing data and variables that will be used for analysis, development of these variables over the time and stationary testing. The third part is dedicated to the regression analysis and includes models for GDP growth, unemployment growth and inflation. The last part of this master thesis will sum up the results and findings of previous parts. The main source for the data used in this work is the statistical database of World Bank (2016).
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses